The cost of double standard risk communication during the swine-flu epidemic: Reflections from Norway - John E. Berg (African Journal of Pig Farming, 2014)
The pandaemia of swine influenza 2009 released a multitude of reactions and actions of public authorities and private enterprises. After the first announcement of a probable new epidemic in May 2009 WHO issued a pandaemia warning in June 2009. Norwegian health authorities reacted swiftly to the WHO recommendations and Norway became the first country opting for buying vaccines for the whole population. The background of the strategy in Norway is described using paper media communications and with reference to television broadcasts. The emanating maximizing and minimizing strategy followed by the Norwegian health authorities was followed. Tests of the swine flu virus were not performed on a scale sufficient to indicate the magnitude of the purported pandaemia. Both strategies were followed simultaneously. WHO indicated in June 2010 that hitherto 18 337 people died of the H1N1 influenza virus compared to some 500 000 from the common flu each year (Aftenposten 25th July 2010, p. 2). More than $ 14 billion had been spent on vaccines and other medical tasks (> $ 750 000 per fatality). In Norway the cost of 9.4 mill. doses of vaccines bought was equivalent to $ 3.7 mill. per fatality in 2009. An initial communication of immense risk and purchase of two vaccine doses for the total population led to rationing of vaccines when people subsequently wanted them. The cost of this decision was far above accepted limits for resource spending on health care. This was followed by communicating a small risk of infection for most of the population. Experts exposed differing views on the developing epidemic. Risk communication from high decision levels was inadequate. Strategies for handling emerging high risk epidemics must be developed and applied in order to reduce fear in the population and huge costs to society